2021
DOI: 10.2147/idr.s335057
|View full text |Cite
|
Sign up to set email alerts
|

Study of Monocyte Subsets and Their Surface Expression of CD86 and Serum IL-17 Compared to Serum Procalcitonin as Markers of Early Neonatal Sepsis

Abstract: Introduction Neonatal sepsis can quickly progress to multi-organ failure with high morbidity and mortality, making early diagnosis mandatory. Although being the gold standard, the long duration of blood culture may lead to hazardous neonatal complications. Sepsis activates monocytes and changes their subset distribution with the resultant activation of lymphocytes and adaptive immune cells changing the plasma cytokines levels. Subjects and Method Percentages of monocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…When examining the remaining CD86 and TIM-3 markers related to the activation or depletion of monocytes, we did not find significant differences between the groups. El Sehmawy et al [51] show that healthy people have lower percentages of monocytes expressing CD86 compared to the COVID-19 patients in our study.…”
Section: Discussionsupporting
confidence: 50%
“…When examining the remaining CD86 and TIM-3 markers related to the activation or depletion of monocytes, we did not find significant differences between the groups. El Sehmawy et al [51] show that healthy people have lower percentages of monocytes expressing CD86 compared to the COVID-19 patients in our study.…”
Section: Discussionsupporting
confidence: 50%
“…Here, using an in vivo SCI model, we showed that the percentage and MFI of BMP4 + circulating monocytes at dpi-3 were markedly higher in SCI rats than in sham rats, indicating that monocytes are an important candidate for the BMP4 upregulation in the circulation. We evaluated CD86 as a marker of activated monocytes based on previous research in which CD86 + monocytes displayed strong capability to present antigen ( Ugurel et al, 2004 ) and initiate lymphocyte activation ( Pinto et al, 2018 ), and were highly correlated with higher levels of inflammatory cytokines ( Nowak et al, 2019 ; El Sehmawy et al, 2021 ). The results showed that BMP4 is more abundantly expressed in the CD86 + monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Asmaa et al.’s study of 30 neonatal sepsis (a total of 60 participates) showed that compared with the control group, CD86 + monocytes in the sepsis group were significantly higher (median 78.4% vs. 24.0%, P < 0.001). When the cutoff value was 36%, the AUROC for early diagnosis of neonatal sepsis was as high as 0.951, and the sensitivity and specificity were 90% ( 26 ). Céspedes et al.’s malaria-associated bacteremia in a rodent model demonstrated a significantly high expression of mast cell-activating cytokines (IL-9 and IL-13).…”
Section: Discussionmentioning
confidence: 99%